Insulin glargine: pharmacokinetic and pharmacodynamic basis of clinical effect - Vadim Valer'evich Klimontov; Natalya Evgen'evna Myakina (Сахарный диабет)
Glargine became the first long-acting insulin analogue. Glargine was designed to meet basal insulin requirements throughout the day with a single injection. Pharmacokinetics of insulin glargine is characterized by biotransformation into metabolites M1 and M2 that transforms the B chain of glargine so it is similar to the B chain of human insulin. Plasma concentrations of active M1 and M2 metabolites have no pronounced peaks during the day, resulting in lower glucose variability and hypoglycaemia risk when compared with NPH insulin. The metabolic activities of M1 and M2 metabolites are similar to the effect of glargine, whereas the mitogenic effects of these metabolites do not exceed the effect of human insulin. Insulin glargine shows a higher affinity for the insulin-like growth factor-1 (IGF-1) receptor when compared with human insulin. Glargine has no proliferative effect in vivo owing to its rapid conversion into metabolites. Pharmacokinetic and pharmacodynamic variability of glargine is comparable to other insulins. These characteristics are important for the clinical efficacy and safety of glargine.